PENINGKATAN PENGETAHUAN , SIKAP DAN PERILAKU TERHADAP ROKOK PADA SISWA SMU DI KELURAHAN PENATIH - N. KM, EKAWATI,; YULIANTI, D.; NOPIYANI, M. SRI; PURNAMA, S.G.; SUBRATA, M.; ALIT, DEWA (Buletin Udayana Mengabdi; Vol 8 No 1 (2009): Volume 8 No.1 – April 2009, 2012)
ABSTRACT The increasing numbers of smokers among adolescent is very worrying. According to the obtained data around 13,2 % from adolescent aged 15-19 years already smoke in this time, if it is not prevented, the number will increase and become a habit, especially for students of SMU. Smoking behaviour of adolescent may result 25 disease types, among otehrs lung cancer, hypertension and heart. It is required, however that campaign of the smoke danger for health, started since early age child, such as Elementary school, Yunior and Senior High Schools. This can be done through the through introducing free smoking area so that students, teachers, the employees are prohibited to smoke no smoking. This activity aim to see the image of knowledge and attitude of SMU concerning with Cigarette. Counseling and adjacent in installation of poster and sticker anti cigarette was the forms of the activty and the results are the knowledge of student of SMU concerning smoking danger still very unadequate after being given counseling, only the knolwledge equal to 6,7% and change of attitude equal to 4% to be able to desist to smoke from active smokers amount 1.3% in SMU N 8 Denpasar.